The Effect of Operational Costs and Production Costs on Profitability at PT. Ultrajaya Milk Industry & Trading Company Tbk. - Galuh Rini; Thomas Sidharta (Penerbit Jurnal Indonesia, 2025)
This study aims to analyze the effect of operating costs and production costs on profitability in PT Ultrajaya Milk Industry & Trading Company Tbk during the period 2018 to 2024. The background of this research is based on the phenomenon of fluctuations in profitability that is not in line with the increase in company revenue, which indicates the influence of cost efficiency on financial performance. This study uses a quantitative method with a descriptive approach and multiple linear regression analysis. The independent variables in this study are operational costs and production costs, while the dependent variables are profitability as measured by the ratios of Return on Assets (ROA), Return on Investment (ROI), and Return on Equity (ROE). The results of the study show that partially or simultaneously, operational costs and production costs have a significant effect on the company's profitability. These findings show that cost management efficiency plays a crucial role in improving a company's ability to generate profits. Thus, the company's management needs to focus its strategy on cost control to support sustainable growth.